FIQH PERSPECTIVES ON HUMAN CORPSE IN CONTEMPORARY TIMES - Meirison Meirison; Susilawati Susilawati; Zerly Nazar (Fakultas Syariah (Syari'ah Faculty ), 2021)
This article discusses some of the contemporary issues and challenges related to handling victims killed in contemporary armed conflicts and situations of violence and other natural disasters within the framework of international humanitarianism in a review of Islamic law. Forensic professionals face problems and challenges in contemporary Muslim contexts, cases, and law: mass burials, quick burials, exhumations, and autopsies. Contemporary scientific discoveries in intensive care units and the rise of industry, which aid in the successful transplantation of organs from cadavers, but reveal new problems from legal, humanitarian, ethical, and judicial perspectives: such as issues of determining the time of death, matters of life (or brain death), and boundaries artificial resuscitation limits, by conducting a literature study and a qualitative descriptive analysis approach, new problems were found in the handling of this corpse, namely, those related to a merciful death, how to injure corpses, the extent of a person's rights over his body after death, cloning of the dead, and so on. Other. These are all doctrinal and not medical matters. The final opinion on this matter is for the jurists; Because that is their specialty, and doctors' views on it are for clarification and reference only. The article concludes that both legal systems have established provisions designed to protect the dignity and respect of the dead and complement each other to achieve this protection in specific contexts and situations involving Muslim parties. Keywords: Human, corpse, fiqh, perspective,